How Housing Affects Stock Investment—An SEM Analysis - Jiandong Li; Jianmei Zhao (Economies, 2019)
The extant literature regarding the effects of housing on stock investment shows inconsistent findings, either positive or negative effects have been reported. This paper investigates the mechanisms by which housing affects household stock investment through a structure equation model (SEM). Applying the data from the China Household Finance Survey (CHFS), we confirm and quantify the magnitudes of contemporaneous “wealth effects„ and “crowd-out effects„ of housing on household equity investment. Overall, the combined effect of housing on stock investment is positive in the context of urban China.